2017
DOI: 10.1136/bcr-2016-216602
|View full text |Cite
|
Sign up to set email alerts
|

Contained ruptured abdominal aortic aneurysm presenting as cauda equina syndrome

Abstract: This is the case report of a contained ruptured aortic aneurysm presenting with acute cauda equina syndrome. The patient was a 79-year-old man. A literature search revealed various unusual presentations of abdominal aortic aneurysm (AAA), including femoral neuropathy, hip pain and others; however, there are no other reports of cauda equina-like syndrome. The present case is therefore another unusual presentation of ruptured abdominal aortic aneurysm and reiterates the utmost importance of careful history takin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The typical triad of acute abdominal or lumbar pain, hypotension, and shock is not present. 5 Patients with chronically contained rupture of aneurysms are hemodynamically stable and have a long history of back or loin pain with symptoms attributable to compressive or erosive effect. 6 In fact, as in this case, the rupture may occur within a contained space such as the retroperitoneum or the psoas muscle space, leading to the patient being stable at presentation and often for longer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical triad of acute abdominal or lumbar pain, hypotension, and shock is not present. 5 Patients with chronically contained rupture of aneurysms are hemodynamically stable and have a long history of back or loin pain with symptoms attributable to compressive or erosive effect. 6 In fact, as in this case, the rupture may occur within a contained space such as the retroperitoneum or the psoas muscle space, leading to the patient being stable at presentation and often for longer.…”
Section: Discussionmentioning
confidence: 99%
“… 6 In fact, as in this case, the rupture may occur within a contained space such as the retroperitoneum or the psoas muscle space, leading to the patient being stable at presentation and often for longer. 5 Booth and Galland 7 reported that the clinical features of contained AAA rupture are vague with back pain in 64% of cases, abdominal pain in 20%, groin pain in 14%, femoral neuropathy in 8%, sepsis in 10%, and asymptomatic in 8%. 4 The clinical presentation may masquerade as metastatic carcinoma, infectious spondylitis, retroperitoneal infection, psoas abscess, and, rarely, obstructive jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…A report by Maki et al described a case of CES which occurred in the aftermath of a lumbar micro-discectomy, where the patient developed symptoms secondary to the shifting of the dural sac caused by ventral epidural venous plexus engorgement which developed as an operative complication [6]. Engamba et al reported a case in which a patient presented with CES which resulted from the rupture of an underlying aortic aneurysm [7]. In a report by Singh et al, an 11-year-old boy was determined to have CES, which resulted from an underlying spinal hydatid cyst, which was initially thought to be an intradural extramedullary benign lesion [8].…”
Section: Discussionmentioning
confidence: 99%